Instructional Leadership in The Development of School Organizational Culture: A Literature Review - Qodiriyah, Qodiriyah (Journal of Quality Assurance in Islamic Education (JQAIE), 2023)
This study is intended to describe how leadership can contribute to the development of organizational culture in schools. Qualitative methodology with a literature approach is used in the study. Data collection is carried out by reviewing and exploring several journals, books, and documents, as well as data sources and other information that is considered relevant to the study. This study found that the principal's instructional leadership prioritizes its activities on learning by influencing, directing, and guiding teachers in teaching and learning activities so that teachers can provide the best learning services to students. With good leadership, the values developed in the school can be passed on culturally to the students well.